Quality of questionnaires for the assessment of otitis media with effusion in children - Wei Chern Gan, Richard; Daniel, Matija; Ridley, Matthew; Barry, Johanna G. (Wiley, 2017)
Objectives Audiometric tests provide information about hearing in otitis media with effusion (OME). Questionnaires can supplement this information by supporting clinical history‐taking as well as potentially providing a standardized and comprehensive assessment of the impact of the disease on a child. There are many possible candidate questionnaires. This study aimed to assess the quality and usability of parent / child questionnaires in OME assessment.